Answer:
g(3)=82
g(-6)=-6632
Explanation:
To find g(3) we are going to use synthetic division for dividing the polynomial x^5-5x^3-10x+4 by x-3.
So this means 3 goes on the outside.
Also since we are missing x^4 and x^2 term, we will need to put a 0 placeholders there.
3 | 1 0 -5 0 -10 4
| 3 9 12 36 78
|_____________________
1 3 4 12 26 82
So g(3)=82
To find g(-6) we will put -6 on the outside:
-6 | 1 0 -5 0 -10 4
| -6 36 -186 1116 -6636
--------------------------------------
1 -6 31 -186 1106 -6632
So g(-6)=-6632